Video Methods, Green Cultural Criminology, and the Anthropocene: SANCTUARY as a Case Study. Issue 4 (3rd April 2018) - Redmon, David
ABSTRACT: Documentary criminology is a burgeoning, open-ended methodological technique that crafts and depicts sensuous knowledge from the lived experiences of crime, transgression, and harm. This 'video ethnography paper' examines my 74 minute documentary, SANCTUARY, as a case study to demonstrate how documentary criminology draws upon green cultural criminology, video methods, and sensory studies to provide an experiential understanding of crime (in this case, against donkeys) and rehabilitation in the contested notion of an 'anthropocene' epoch. I trace how documentary criminology can evoke and enact the lived experiences of "donkey rehabilitation" as sensuous scholarship.